Application of the Linear Congruent Method in Online Exams in English: Penerapan Linear Congruent Method Pada Ujian Online - Hermawan, Agus; Susanti*, Wilda; Tendra, Gusrio; Duha, Yermias (Digital Zone: Jurnal Teknologi Informasi dan Komunikasi, 2023)
The Corona Virus (Covid-19) outbreak has had an impact on the education sector. This impact affects the delay in the student learning process. Because of this situation, technology that has developed significantly can be directed to make exams online, replacing conventional exams. Carrying out conventional exams requires time, effort and paper. Teachers cannot make assessments quickly and precisely, this will hinder the ranking of grades and of course affect the ranking of students in class. Exams in the form of paper allow cheating by students. Therefore, an online-based exam system was built. The online exam is designed using the Linear Congruent Method (LCM). The method used in the online exam system is the Linear Congruent Method (LCM). The built online exam can generate numerical randomization (modulo) from the process of students taking the exam in LCM calculations so that each student will get a different order of questions. Students will get the results of the answers automatically after completing the problem. The results of this study were tested by working on 50 questions at the Dharma Loka High School, with an accuracy rate of up to 100% using the randomization calculation process (modulo).